COMPARISON OF PERINEAL WOUND HEALING WITH CHERRY LEAF EXTRACT GEL AND MORINGA LEAF EXTRACT GEL - Rike Wahyuni Dwi Aprianti; Indria Nuraini; Yuni Khoirul Waroh (Jurnal Kebidanan Indonesia, 2026)
Background: Perineal rupture can increase the risk of infection due to bacterial entry through the torn tissue if not properly treated. Cherry leaf extract gel (Muntingia calabura L.) and moringa leaf extract gel (Moringa oleifera) are natural treatment alternatives that contain flavonoids with anti-inflammatory and antimicrobial properties, which can accelerate tissue regeneration and perineal wound healing.Methods: This study aimed to determine the difference in effectiveness between cherry leaf extract gel and moringa leaf extract gel in healing perineal wounds. This quasi-experimental study used a pre-posttest two-group design with purposive sampling involving 32 respondents.Results: The intervention was administered twice daily after bathing at a dose of 5 grams for 7 days. The results showed that in the cherry leaf extract gel group, 12 respondents (75%) had good wound healing with an average REEDA scale of 0.50. Meanwhile, in the moringa leaf extract gel group, 7 respondents (43.8%) showed good healing with an average REEDA scale of 3.18. Normality and homogeneity tests indicated the data were normally distributed and homogeneous (p > 0.05). The paired t-test showed a significant difference before and after the intervention in both groups (p < 0.05). The independent t-test revealed a significant difference in effectiveness between the two groups (p = 0.035).Conclusion: In conclusion, cherry leaf extract gel is more effective than moringa leaf extract gel in accelerating perineal wound healing. It is recommended that healthcare services consider the use of these non-pharmacological therapies for postpartum mothers experiencing perineal rupture. Keywords: Cherry leaf extract gel; moringa leaf extract gel; perineal wound;postpartum mother; REEDA